Cobalt-Catalyzed Regio- and Enantioselective Hydroalkylation of 1,1-Disubstituted Styrenes - Li, Yan; Lu, Xi (Synlett, 2024)
The metal hydride catalyzed alkene hydroalkylation enables efficient alkyl–alkyl coupling, yielding structurally diverse chiral organic compounds. However, the control of stereochemical selectivity in alkene hydroalkylation still heavily relies on the assistance of substrate Lewis basic functional groups or polar heteroatom functional groups. We have recently developed a cobalt hydride catalytic system and established a paradigm of enantioselective control assisted by C–H···π noncovalent interactions. This approach enables the asymmetric hydroalkylation of 1,1-disubstituted styrenes, thereby circumventing the limitations imposed by substrate heteroatom functional groups.1 Introduction2 Reaction Development3 Synthetic Applications4 Mechanistic Investigation5 Conclusion and Future Outlook
Keywords: cobalt catalysis; asymmetric catalysis; alkyl–alkyl coupling; alkene hydroalkylation; 1,1-disubstituted styrenes; C–H···π interaction